Welfare state survey 1986 - Svallfors, Stefan (Umeå University, 1992)
The questionnaire used in this survey was constructed to fulfill several purposes. Firstly the aim was to follow up some of the questions posed in previous Swedish surveys. Secondly the aim was to capture both attitudes to the general political debate about the welfare state and opinions about more specific areas within the welfare political area. Thirdly the aim of the questionnaire was to explain attitudes to different aspects of the welfare politics: what areas did one want to invest money in, who was most suited to take care of different services, how should the welfare state be financed, and if one suspected that there were suspicions of misuse of benefits and services. Based on a theorization of different “welfare political dimensions” the aim was to capture both the nuances and ambivalences that the attitudes to the welfare politics could contain.

Frågeformuläret som användes vid denna undersökning konstruerades för att fylla olika syften. För det första ville man följa upp några av de fåtaliga frågor som tidigare ställts i andra svenska undersökningar. För det andra var avsikten att fånga både attityder till den allmänna politiska debatten kring välfärdsstaten och åsikter kring mer specifika välfärdspolitiska områden. För det tredje skulle frågeformuläret klargöra attityder till olika aspekter av välfärdspolitiken: vilka områden man ville satsa pengar på, vem man ansåg bäst lämpad att sköta olika tjänster, hur man ville finansiera välfärdspolitiken och om man misstänkte att det förekom missbruk av bidrag och tjänster. Utifrån en teoretisering av olika 'välfärdspolitiska dimensioner' ville man få fram de nyanser och ambivalenser som attityder till välfärdspolitiken kunde innehålla.
Välfärdsstatsundersökningen 1986
Åsikter om den offentliga sektorn 1986
Keywords: public sector; offentlig sektor; care of the elderly; äldreomsorg; fiscal policy; skattepolitik; social welfare; social välfärd; public expenditure; offentlig utgift; social welfare expenditure; utgift för social välfärd; educational expenditure; utbildningsutgift; child care; barnomsorg; medical care; sjukvård; public services; offentlig service; privatization; privatisering; taxation; beskattning; social security benefits; socialförsäkringsförmåner; education; utbildning; social welfare finance; finansiering av social välfärd; welfare economics; välfärdsekonomi; social welfare philosophy; social välfärdsfilosofi; Economic policy, public expenditure and revenue; Ekonomisk politik, offentliga utgifter och intäkter; Social welfare policy; Välfärdspolitik; Social welfare systems/structures; Sociala välfärdssystem/-strukturer; Specific social services: use and availability; Specifika sociala tjänster: användning och tillgänglighet; Social behaviour and attitudes; Socialt beteende och attityder; Social Sciences; Samhällsvetenskap; Sociology; Sociologi